Comparison of the Effect of Proprioceptive Neuromuscular Facilitation Exercises with Mental Imagery and Working Memory on Dynamic Balance, Range of Motion and the Rate of Spasticity in MS Patients - Ebrahimi, Mohammad; Mousavi Sadati, Seyed Kazem; Daneshjoo, Abdolrasoul (Journal of Clinical Physiotherapy Research, 2020)
Introduction: The purpose of this study was to compare the effects of Proprioceptive Neuromuscular Facilitation (PNF) exercises with mental imagery and working memory and combining these two types of exercises on dynamic balance, range of motion, and spasticity of Multiple sclerosis (MS) patients. Method and Materials: In this quasi-experimental study, 30 male MS patients were randomly assigned into three groups (n=10) of PNF, mental imagery and working memory training, and combination. The study included pre-test, intervention, and post-test. Timed Up and Go test, range of motion, and rate of muscles spasticity in active and passive extension of knee were measure in pre-test, and post-test. Intervention consisted of 6 weeks of exercise in each group. Data were analyzed using Paired Samples t-test, ANCOVA, Kruskal-Wallis, and Wilcoxon Signed Ranks Test. Results: The results showed that each of mental imagery and working memory training, and combination had a significant effect on dynamic balance (P<0.01), range of motion of passive and active knee extension (P<0.01) and spasticity of passive and active knee extension (P<0.01) in MS patients. No significant differences were found between training groups in any of the variables (P>0.05). Conclusion: Overall, the results of the present study showed that PNF, mental imagery, working memory, and combined training can be used to improve balance, range of motion, and spasticity of MS patients.